2021
DOI: 10.1186/s12876-021-01808-3
|View full text |Cite
|
Sign up to set email alerts
|

Manometrically jackhammer esophagus with fluoroscopically/endoscopically distal esophageal spasm: a case report

Abstract: Background Jackhammer esophagus is a rare esophageal motility disorder that can result in dysphagia, chest pain, and gastro-esophageal reflux symptoms. High-resolution manometry is the gold standard for diagnosis, while corkscrew esophagus on upper gastrointestinal endoscopy is an uncommon manifestation. Case presentation 72-year-old man who presented with progressive dysphagia for three months without symptoms of chest pain or heartburn. Initial w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Thus, for patients with persistent GERD symptoms, prompt HREM and 24-hour pH impedance monitoring should be considered to evaluate PPIs effectiveness. Nifedipine is recognized as a potential therapeutic option for JE symptoms [13]. Several studies have shown Deanxit to be beneficial for JE patients with EGJ Outflow Obstruction (EGJOO) unresponsive to combined PPIs and nifedipine treatment [14].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, for patients with persistent GERD symptoms, prompt HREM and 24-hour pH impedance monitoring should be considered to evaluate PPIs effectiveness. Nifedipine is recognized as a potential therapeutic option for JE symptoms [13]. Several studies have shown Deanxit to be beneficial for JE patients with EGJ Outflow Obstruction (EGJOO) unresponsive to combined PPIs and nifedipine treatment [14].…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to GERD, it might be of benefit to perform pH monitoring in those with predominantly typical or atypical reflux symptoms and to repeat HRM after anti-reflux treatment, as manometric findings may improve [ 1 - 2 , 7 , 9 , 11 ].…”
Section: Reviewmentioning
confidence: 99%
“…As there have not been any prospective studies addressing the treatment of HE, its management approach is yet to be validated. Pharmacotherapy including calcium channel blockers, nitrates, phosphodiesterase-5 inhibitors, anticholinergics, and low dose antidepressants is effective in a subset of patients with HE, but lacks longterm follow-ups to assess the efficacy of these drugs [14,15]. Interventional procedures such as botulinum toxin injection, pneumatic dilation and per-oral endoscopic myotomy (POEM) show favorable results when patients are refractory to medications [5,16,17].…”
Section: Case Presentationmentioning
confidence: 99%